Resource Use And Plant Interactions In A Rice-Mungbean Intercrop - Aggarwal, P.K.; Garrity, D.P.; Liboon, S.P.; Morris, R.A. (Wiley, 1992)
Intercropping of upland rice (Oryza sativa L.) with short‐duration grain legumes has shown promising productivity and resource use efficiency. To better understand intercrop relationships, we used aboveand underground partitions, residue removal, and plant removal to investigate the interactions between upland rice (120‐d crop duration) and mungbean [Vigna radiata (L) Wilczek, 65‐d crop duration]. Treatments were evaluated during two rainy seasons on an unfertilized Typic Tropudalf at Los Baños, Philippines. Nitrogen uptake by intercropped rice (33.4 and 41.1 kg N ha−1) approximated that of sole rice (35.4 and 38.1 kg N ha−1). Intercropped rice yielded 73 to 87% of sole rice and intercropped mungbeans yielded 59 to 99% of sole mungbean. Root barriers did not affect rice N uptake or dry matter accumulation prior to the maturity of the mungbean, but reduced N uptake, dry matter, and grain yields substantially by the time of rice harvest. Sole rice with every third row removed at mungbean harvest had N, grain, and dry matter yields similar to the intercropped rice with every third row occupied by the legume. Sole rice with every third row vacant during the entire growing season yielded similarly (2.6 Mg h−1) to sole rice (2.3 Mg h−1) and intercropped rice (2.0 Mg h−1). There was no evidence that N transfer from the legume to the rice increased N availability to rice above that expected with a sole rice crop with the same planting scheme. Rice yield compensation in the intercrop was apparently due to the increased soil volume for N extraction and increased aerial space available after mungbean harvest.